Pengaruh frekuensi menonton drama korea, kebiasan makan, dan pendidikan terhadap kualitas diet dan status gizi mahasiswa Politeknik Negeri Balikpapan - Praseptia Gardiarini; Chardina Dianovita; Farida Farida (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Korean drama is a type of entertainment that is popular with many groups, one of which is students.  The quality of a student's diet is related to what they consume, the frequency and adequacy of the food consumed. The nutritional status of students can vary due to their eating habits and daily patterns. It is necessary to know how much influence these factors have on students' nutritional status.Objective: This study aims to determine the influence of frequency of watching Korean dramas, eating habits, level of education on diet quality and nutritional status using path analysis.Method: This research used a quantitative descriptive design with a cross-sectional method, carried out for three months (July-September) 2022 at the Poltekba campus, involving 81 respondents, first-level and second-level culinary arts students, with samples taken using a purposive sampling technique. Data were analyzed using univariate tests to describe descriptive data and multivariate using path analysis to see the influence between variables.Results: The results stated that eating habits affect the quality of diet and nutritional status of students (p=0.03). While Korean dramas, and education significantly have no effect.Conclusion: Eating habits can directly influence diet quality, but korean dramas, education level and diet quality do not affect the nutritional status of students.KeywordsKorean Drama, Diet Quality, Path Analysis